MEMBANGUN KESEHATAN MENTAL SELAMA PANDEMI COVID-19 DENGAN KREATIVITAS SISWA PONDOK PESANTREN TAHFIDZ QURAN MASSAROTUL, KOTA SERANG - Linardita Ferial (ABDIKARYA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2021)
The COVID-19 pandemic that has hit the whole world and Indonesia has had a huge impact, especially in the field of education, where many students have decreased their mental health due to lack of activity so that the aim of this community service is to reduce student stress levels in an effort to build mental health with creativity during the COVID-19 pandemic, which was located at the Massarotul Muhtajin Tahfidz Qur'an Islamic Boarding School, Serang City. Community service uses a workshop approach using lectures, discussions and exercises with making souvenirs with 60 participants. The results of the dedication show that the number of participants who are enthusiastic about the activity, as many as 80% of the participants already understand and can be creative in making souvenirs so that it can reduce stress levels so that this training can foster a spirit of creativity in the participants in an effort to improve mental health.